Penerapan Aromaterapi Peppermint Pada Pasien Kanker Yang Menjalani Kemoterapi Dengan Masalah Keperawatan Nausea - Rahmi, Fadhila; Kharisna, Dendy; Wardah, Wardah; Dewi, Sarina (Yayasan Healing and Healthcare Education, 2024)
Cancer is a life-threatening disease with the prevalence rate increasing every year. Nursing problems that can arise are nausea. Treatment of nausea and vomiting can be done non-pharmacologically by providing peppermint aromatherapy. The aim of this research is to provide an overview of the results of professional practice by applying peppermint aromatherapy to reduce nausea and vomiting in patients undergoing chemotherapy. The number of respondents was 2 people. The application of peppermint aromatherapy is carried out 3 times a day for 3 days. The measuring tool used is The Index of Nausea, Vomiting, and Retching (INRV) questionnaire. During the time the author provided nursing care, there was a change in patient 1's score from the moderate category (Total score 13) to the mild category (Total score 6). Patient 2 went from the moderate category (total score 12) to the mild category (total score 5). Based on this, the application of peppermint aromatherapy is able to overcome the problem of nausea and vomiting which is characterized by a decrease in the frequency score of nausea and vomiting in cancer patients undergoing chemotherapy.